Soil microbial biomass and activity under the influence of lead addition and mycorrhizal soybean rhizosphere - Andrade, Sara Adrián López de; Silveira, Adriana Parada Dias da (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the effects of lead addition on soil microbial biomass and activity under the influence of the rhizosphere of mycorrhizal soybean. The experimental design was completely randomized and arranged in a 4x2x2 factorial scheme, using 0, 150, 300 and 600 mg dm-3, inoculation or not of the arbuscular mycorrhizal fungus (AMF) Glomus macrocarpum and two sampling periods: soybean flowering and maturity. Microbial biomass C, soil respiration and the activity of three soil enzymes (deshydrogenase, alkaline phosphatase and arilsulphatase) were determined. The most affected enzyme was alkaline phophatase, whose activity was reduced in 60%, and which was a sensible indicator of the microbial metabolic stress caused by high Pb concentrations. Soybean mycorrhization directly influenced the rhizospheric microbiota leading to higher activity and biomass, mainly at soybean maturity stage. Soil microbiota showed stress symptoms due to Pb addition to soil.